2021
DOI: 10.3390/biology10020139
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanins Are Key Regulators of Drought Stress Tolerance in Tobacco

Abstract: Abiotic stresses will be one of the major challenges for worldwide food supply in the near future. Therefore, it is important to understand the physiological mechanisms that mediate plant responses to abiotic stresses. When subjected to UV, salinity or drought stress, plants accumulate specialized metabolites that are often correlated with their ability to cope with the stress. Among them, anthocyanins are the most studied intermediates of the phenylpropanoid pathway. However, their role in plant response to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 62 publications
(90 reference statements)
5
47
0
Order By: Relevance
“…Anthocyanins are a class of different non-photosynthetic water-soluble pigments derived from flavonoids via the shikimic acid pathway [17]. Their biosynthesis is elicited by a number of abiotic stresses, including drought stress [45]. They may function as a screen to increase photoprotection and as a pool of antioxidant metabolites [46].…”
Section: Discussionmentioning
confidence: 99%
“…Anthocyanins are a class of different non-photosynthetic water-soluble pigments derived from flavonoids via the shikimic acid pathway [17]. Their biosynthesis is elicited by a number of abiotic stresses, including drought stress [45]. They may function as a screen to increase photoprotection and as a pool of antioxidant metabolites [46].…”
Section: Discussionmentioning
confidence: 99%
“…The LMA was evaluated on nine leaves per treatment as the ratio between leaf DW and leaf area. The number of epidermal cells and stomata were determined on the abaxial and adaxial sides of the same leaves used for leaf gas exchange and LMA measurements, as described by Cirillo et al [68]. Briefly, leaf impressions were made using cyanoacrylate glue on a microscopy slide.…”
Section: Morpho-anatomical Leaf Traits Determinationmentioning
confidence: 99%
“…Anthocyanins act in stress response by increasing the solute content in the vacuoles thereby lowering the osmotic potential of the leaf [27]. Additionally, it was shown that anthocyanins' accumulation led to a metabolic shift in leaves with respect to amino acids and non-structural carbohydrates: proline content increased together with starch reserves' use to provide carbon skeletons required for the synthesis of metabolites involved in osmotic adjustment [28]. With an increasing salt concentration, a purple coloration started to develop rapidly in the epidermal layer of the abaxial side of leaves (Figure 2).…”
Section: Effects Of Increasing Salt Concentrations On Micro-tom Leaves and Stemsmentioning
confidence: 99%